Monetary persistence, imperfect competition, and staggering complementarities - Christian Merkl; Dennis J. Snower (Kiel Institute for World Economics (IfW), 2005)
This paper explores the influence of wage and price staggering on monetary persistence. First, our analysis indicates that the degree of monetary persistence generated by wage vis-à-vis price staggering depends on the relative competitiveness of the labor and product markets. We show that the conventional wisdom that wage staggering can generate more persistence than price staggering does not necessarily hold. Second, this paper discusses weaknesses of the contract multiplier, which is generally used to compare persistence, and proposes the measure quantitative persistence. Third, we show that, for plausible parameter values, wage and price staggering are highly complementary in generating monetary persistence. Thus beyond understanding how they work in isolation, it is important to explore their interactions.
Keywords: E40; E52; E50; 330; Price Staggering; Wage Staggering; Monetary Policy; Monetary Persistence; Geldpolitik; Schock; Hysteresis; Lohnrigidität; Preisrigidität; Unvollkommener Wettbewerb; Theorie